Limited responses of lizard assemblages to experimental fire regimes in an Australian tropical savanna - Angga Rachmansah; Keith Christian; Kimberley Day; Brett P. Murphy; Christine Schlesinger; Chava L. Weitzman; Alan N. Andersen (Ecology, 2025)
Disturbance is fundamental to ecosystem dynamics, and its management is foundational to effective ecosystem management for the conservation of biodiversity. Fire is a key agent of disturbance influencing faunal communities in many terrestrial ecosystems, and it underpins the conservation management of fire‐prone ecosystems. However, we have a limited understanding of how faunal communities in fire‐prone ecosystems respond to variation in fire frequency. Here, we use a long‐term fire experiment to investigate the effect of fire frequency on lizard assemblages in an Australian tropical savanna. We sampled lizards using pitfall traps, funnel traps, and direct searches in replicate ( n = 3) 1‐ha plots that had been burnt every 1, 3, or 5 years or left unburnt for 18 years. We found no significant variation in total lizard abundance or the collective abundances of mesic, semiarid, or widespread biogeographic groups. The abundance of only one of the five most common species was significantly related to fire frequency. Species richness decreased with increased fire frequency and showed a humped relationship with woody cover. Species composition was slightly better explained by variation in woody cover than by fire frequency, with both effects relatively weak. Although woody cover declined with increasing fire frequency, it varied markedly both within and among plots experiencing the same fire treatment, which explains why fire frequency was not as strong a predictor of variation in lizard assemblages as woody cover. Our findings show that the diverse lizard assemblage in our tropical savanna system exhibits a very limited response to variation in long‐term fire frequency and attribute this to the marked small‐scale variation in woody cover that was inherent under any fire treatment. We conclude that small‐scale patchiness in vegetation cover plays a critical role in the responses to fire of faunal species with relatively small foraging territories, reducing a need for larger scale fire mosaics under a “pyrodiversity begets biodiversity” paradigm.